Optimization of Transportation Distribution Costs Using Improved Vogel's Approximation Method (IVAM) (Case Study: PT. Sinar Putra Pertam) - Mussafi, Noor Saif Muhammad; Adianta, Alya (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Distribution is the process of distributing goods from source to destination. The main problem with distribution is the inefficiencies in distribution costs. The distribution problem can be solved by transportation methods. The transportation method is carried out in two stages, namely finding the initial solution then looking for the optimal solution. This study uses Improved Vogel's Approximation Method (IVAM) initial solution method and Modified Distribution Method (MODI) as the optimal solution method in distributing 3 Kg LPG gas PT. Sinar Putra Pertam. This study aims to find out how IVAM and MODI work in getting optimal solutions, and compare the results of these calculations with the calculation of 3 Kg LPG gas distribution costs from the company. In this study, there were 2 sources of LPG gas filling which were distributed using a fleet of colt trucks to 15 destinations. The distribution cost is calculated based on fleet fuel consumption. The results of the initial solution calculation show IVAM requires three iterations to get a solution. While the calculation results of the MODI optimization test require one iteration to achieve the optimal solution. The distribution cost using IVAM and MODI is the same amounting to IDR 6,816,230.00 so that it is smaller than the conventional calculation results from the company, which is IDR 9,307,000.00. Based on these results, the transportation method used in this study can save 26.76% of the total distribution cost.